Measuring the progress of a recovery process after an earthquake: The case of L'aquila, Italy. (June 2018) - Contreras, Diana; Forino, Giuseppe; Blaschke, Thomas
Abstract: After the earthquake in 2009, L'Aquila (Italy) began a recovery process characterized by a delay in the reconstruction of the city center. Between 2010 and 2014 a recovery index was formulated based on spatial indicators, such as building condition and building use, to measure the progress of the recovery process in L'Aquila. Eight years after the earthquake, the work presented in this paper was used to update the recovery index, not only by measuring the progress of the recovery in L'Aquila but also by validating the usefulness of the proposed recovery index. To achieve this objective, the current research considered the same set of spatial indicators that were used to determine the progress of the recovery in L'Aquila by 2010, 2012, and 2014 in the revaluation of the expert criteria. It was found that in 2016 the number of reconstructed buildings and buildings under ongoing construction had significantly increased and the number of buildings with residential and commercial use had increased along the main roads. While progress was observed in the overall building condition, there was no significant progress in the building use. This poses several questions about how the recovery process can contribute to the return of the inhabitants to the city center of L'Aquila. The paper concludes that the proposed recovery index is useful for identifying the spatial pattern of the recovery process in an urban area affected by an earthquake. At the same time, this recovery index allows the recovery progress to be quantified based on indicators.